شيخ حاج عبد الله بن حاج عبد اللطيف – فطاني سلاتن تايلند - Abdulloh Salaeh; Nidzamuddin Zakaria; Muhammad Widus Sempo; Syed Mohammad Chaedar Syed Abdurrahman Al Yahya; Imran Bin Abdul Halim; Mohd Fauzi Mohd Amin; Eddie ibn Mohdi Al-Fattan; Farida Haji Teh (Universiti Sains Islam Malaysia, 2024)
E-PROSIDING KONVENSYEN KEARIFAN NUSANTARA KE-3 ARIF 2021 “MEMARTABATKAN KEARIFAN MELAYU ISLAM NUSANTARA” / Disunting oleh: Muhammad Widus Sempo, Shumsudin Yabi, Abdulloh Salaeh, Syed Najihuddin Syed Hassan, Nurul Athirah Syamila Sulaiman. Anjuran: Fakulti Pengajian Quran Dan Sunnah & Madrasah Ahmadiah Islamiah, Narathiwat, Thailand 17 Ogos 2021